Pengembangan Perangkat Pembelajaran Flipped Classroom Berbasis Tri-N pada Pokok Bahasan Bangun Datar di SMP - Shalihah, Hanin Hanifah Rahmatu; Arcana, I Nyoman; Sukiyanto, Sukiyanto (MATHEdunesa, 2025)
This research is based on the importance of mathematics in life, the importance of learning media with a variety of learning models, and the rapid development of technology. This research aims to produce a Tri-N based flipped classroom learning media that is appropriate to the subject of Flat Build in junior high school and determine the feasibility of the Tri-N based flipped classroom learning media produced in this research. This research uses development research methods, with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model. This research was carried out at SMP Negeri 2 Sanden with the research subjects being class VII F students, totaling 31 students. The research instruments used were validation questionnaires, student response questionnaires, and learning outcomes tests. The data analysis techniques used are practicality tests, effectiveness tests, and correlation tests. The results of this research are learning media in the form of teaching modules, e-modules, LKPD, learning videos and test questions. The characteristics of this learning media are: teaching module with a flipped classroom learning model equipped with a learning video link and e-module link, the e-module is equipped with a link and barcode to access the video, activities on the LKPD are in accordance with the Tri-N principle. This learning media is declared feasible for use in learning. The feasibility is supported by the results of validation with a very valid category and the results of student response questionnaires in the good category. In addition, based on the results of the learning outcomes test, the percentage of students who meet the KKM is in the effective category. The correlation result between the student response questionnaire and the learning outcomes test is significant and in the same direction, meaning that the high student response questionnaire score, are followed by high learning outcomes test score. In other words, the use of learning media affects students learning achievement. From the research results that have been presented, further researchers can implement the development of flipped classroom learning devices on other materials.